Psychological factors as predictors of proneness to teenage pregnancy among public secondary school students in Ibadan, Oyo State (2020)
Teenage pregnancy is one of the socio-economic challenges confronting this millennium. Therefore, this study explored the proneness of girls to pregnancy and the proneness of boys to impregnating the girls, The study is a correlational research type. The sample comprised 1200 respondents from 12 public secondary schools in Ibadan (six from city and less city each), Oyo State. Two instruments namely Psychological Factors Questionnaire PFO (α = 0.68) and Proneness to Teenage Pregnancy Questionnaire of boys and girls to pregnancy PTPQ with (α ,0.67) and (α =0.60) respectively used to collect data from the respondents and data collected were analyzed using multiple regression analysis. All the predictors accounted for 55% of the variance observed in proneness of boys to impregnating girls and 31% of variance observed in proneness of girls to pregnancy. Parental attitude contributed most significantly to the prediction of proneness of boys to impregnating the girls while students' attitude contributed most significantly to the prediction of girls' proneness to pregnancy. Based on the findings, it is recommended that sexuality education should be effectively taught at secondary school level so as to instill in the students' the necessary values that make them abstain from premarital sexual activities.